(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
The farmers of our country mostly depend on chemical pesticides for crop protection due to the scarcity of competent pesticide alternatives and enough knowledge of safe pest management. As a result, there is a great possibility to remain residues in the harvested crops. Keeping this view, this study was conducted to analyze organophosphorus pesticide residues in yard long bean collected from five local markets of Mymensingh district of Bangladesh. The collected samples were carried to the Pesticide Analytical Laboratory, Entomology Division of Bangladesh Agricultural Research Institute (BARI), Gazipur on the same sampling day. The collected samples were analyzed using Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and Gas Chromatography (GC) coupled with Flame Thermionic Detector (FTD). Among the 30 samples of yard long bean, 3 samples (10% of the total samples) contained residue of quinalphos, of which 2 samples contained quinalphos residue above MRL. This study reflects the overall scenario of pesticide residue remain in the harvested yard long bean collected from local markets of Mymensingh city. Therefore, monitoring of pesticide residues in vegetables should be strengthened. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (1), 8-16